From defense to offense: Modulating toll-like receptors to combat arbovirus infections - Rafidah Lani; Ilya Maisarah Thariq; Nuramira Syazreen Suhaimi; Pouya Hassandarvish; Sazaly Abu Bakar (Taylor & Francis Group, 2024)
ABSTRACTArboviruses are a significant threat to global public health, with outbreaks occurring worldwide. Toll-like receptors (TLRs) play a crucial role in the innate immune response against these viruses by recognizing pathogen-associated molecular patterns and initiating an inflammatory response. Significantly, TLRs commonly implicated in the immune response against viral infections include TLR2, TLR4, TLR6, TLR3, TLR7, and TLR8; limiting or allowing them to replicate and spread within the host. Modulating TLRs has emerged as a promising approach to combat arbovirus infections. This review summarizes recent advances in TLR modulation as a therapeutic target in arbovirus infections. Studies have shown that the activation of TLRs can enhance the immune response against arbovirus infections, leading to increased viral clearance and protection against disease. Conversely, inhibition of TLRs can reduce the excessive inflammation and tissue damage associated with arbovirus infection. Modulating TLRs represents a potential therapeutic strategy to combat arbovirus infections.